HIMPUNAN BILANGAN BULAT NON NEGATIF PADA SEMIRING LOKAL DAN SEMIRING FAKTOR - Fatimah, Meryta Febrilian; Puspita, Nikken Prima; ., Farikhin (MATEMATIKA, 2014)
Let commutative Semiring S. Ideal on Semiring S defined in the same way with the Ideal on the ring. On Semiring Â there are special Ideals such as -ideal, -maximal Ideal and -ideal. Semiringwith a unique -maximal Ideal is called local Semiring. In This paper we will discussed that from non negative integer Â we can determined a local Semiring and quotient Semiring.